ISPC Commentary on the Revised Proposal for CRP2 - November 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the revised proposal for CRP 2: Policies, Institutions and Markets to strengthen Food Security and Incomes for the Rural Poor (Revision of October 2011).